2001
DOI: 10.1002/esp.210
|View full text |Cite
|
Sign up to set email alerts
|

Modelling three‐dimensional flow structures and patterns of boundary shear stress in a natural pool–riffle sequence

Abstract: Fluid-sediment interactions control river channel forms and processes. Analysis of spatial hydraulic patterns and the resulting boundary shear stress are required to aid understanding of river system behaviour. In this paper, the hydraulic processes active in a natural pool-riffle sequence are simulated using a three-dimensional computational fluid dynamics (CFD) model. Methods employed for the prescription of model boundary conditions are outlined. Model calculations are assessed using comparisons with field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
150
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(168 citation statements)
references
References 39 publications
13
150
3
Order By: Relevance
“…Cao et al [2003] conclude that a channel constriction can, but may not necessarily, lead to [sediment transport] competence reversal, depending on channel geometry, flow discharge, and sediment properties. Booker et al [2001] conclude that an analysis of near-bed velocity patterns suggested that the near-bed flow direction can cause routing of sediments away from the deepest part of the pools. Their results indicate maintenance of pool-riffle morphology by a lack of sediment being routed into pools rather than an increased ability to erode based on convergence of flow into the pool.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Cao et al [2003] conclude that a channel constriction can, but may not necessarily, lead to [sediment transport] competence reversal, depending on channel geometry, flow discharge, and sediment properties. Booker et al [2001] conclude that an analysis of near-bed velocity patterns suggested that the near-bed flow direction can cause routing of sediments away from the deepest part of the pools. Their results indicate maintenance of pool-riffle morphology by a lack of sediment being routed into pools rather than an increased ability to erode based on convergence of flow into the pool.…”
Section: Introductionmentioning
confidence: 77%
“…Their study demonstrated how the upstream constriction resulted in higher local velocities in the pool in comparison to adjacent riffles, despite a similar cross-sectional area. As noted by Booker et al [2001], this concept links the concept of velocity reversal with work by Keller [1972] which suggested that the regular pattern of scour and deposition required for pools and riffles may be provided by an alternation of convergent and divergent flow patterns along the channel. This connection is significant because the pool-riffle sequence on Dry Creek has a point bar (on the north bank between sections 22 and 20 on Figure 1) which acts as constriction at the head of the pool.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recent studies utilizing 2D and 3D hydraulic models have demonstrated the dominant role of nonuniform flow, secondary circulation patterns, and coherent turbulent structures influencing pool-riffle maintenance processes [152][153][154][155][156][157][158][159]. Expanding to a multidimensional view of hydraulics and sediment routing through pool-riffle, morphological maintenance is explained by flow acceleration at the pool head's cross-sectional constriction during high flows, where flow convergence with maximum velocities and sediment are directed over the point bar rather than the pool thalweg.…”
Section: Applied Geomorphic Processes For Mesohabitat Maintenancementioning
confidence: 99%
“…This classification scheme recognized the fluvial dynamics of a geomorphic bar unit by incorporating the Bar Unit Concept [36]. As a single geomorphic unit consisting of pool-riffle-bar morphology, the fluvial dynamics is characterized by a 3D convergent-divergent helical flow pattern [147,149,150,153]. In riffles during low flow, downstream-directed velocities accelerate slightly from the reduced water depth, and turbulence is moderate in relative comparison to high TKE observed in the front of pool [152,156].…”
Section: Submerged Barmentioning
confidence: 99%